Comparative evaluation of cows of different lineages according to their productivity and reproductive qualities - S. V. Titova (Аграрная наука Евро-Северо-Востока, 2024)
The article presents the results of a comparative study of the milk productivity and reproductive ability of the first-calf cows of the black-and-white Holstein breed in the context of genealogical lines. The initial material was information from the primary zootechnical and breeding records of cows (n = 3211). For comparative analysis, groups of animals were formed in accordance with their linear affiliation: the first group – individuals of the Vis Beck Ideal 1013415 line, the second – the Montwick Chieftain 95679 line, the third – the Reflection Sovering 0198998 line. It was found that the animals of the  V. B. Ideal line differed in the highest coefficient of lactation (1363 kg) and the coefficient of lactation constancy (93.2 %). According to the level of milk yield between the groups, the differences were not significant. Cows of the R. Covering line had the best indicators of reproductive ability. They had the lowest age of first fruitful insemination (16.7 months) and calving (26.8 months), as well as the shortest interbody period (13.4 months). They also outperformed the animals of the compared lines in terms of reproductive ability (0.91) and fertility index (46.3). In terms of calf yield per 100 heads (82.8 %), the best were cows of the M. Chieftain line. In all lines, positive correlation coefficients were obtained between milk yield and service and interbody periods (+0.237...+0.278), which indicate that with an increase in milk yield, the duration of service and interbody periods increases, and this indicates a process of deterioration in the reproductive abilities of cows. Cows were evaluated according to the fertility index (according to I. Dokhi). It was found that cows with a rating of "good" fertility, compared with animals rated "medium" and "low", had lower milk yield, shortened duration of the service period and increased reproductive ability. The line of R. Sovering was distinguished by the largest number of cows (56.9 % heads) with good reproductive ability, the average value of the fertility index was 51.2. The presence of low negative correlation coefficients between the fertility index and milk yield, against the background of an increase in milk yield, indicates a decrease in the fertility of cows.